Antimicrobial resistance patterns of Gram-negative bacteria isolated from bloodstream infections in an Iranian referral paediatric hospital: A 5.5-year study. (December 2017) - Mahmoudi, Shima; Mahzari, Masoumeh; Banar, Maryam; Pourakbari, Babak; Haghi Ashtiani, Mohammad Taghi; Mohammadi, Mohsen; Keshavarz Valian, Sepideh; Mamishi, Setareh
Highlights: Study of Gram-negative bacteria (GNB) causing bloodstream infections (BSIs) in Iranian children. K. pneumoniae, E. coli, S. marcescens, P. aeruginosa and Enterobacter spp. were the most common GNB isolated from BSI. An increasing trend in antibiotic resistance among GNB causing BSI in children was observed. The highest rate of GNB (44.5%) was found in the ICU, especially the CICU (22%). Abstract: Objectives: Bloodstream infections (BSIs) are a major cause of paediatric morbidity and mortality worldwide. This study describes the epidemiology and antimicrobial resistance of Gram-negative bacteria (GNB) from BSIs in children admitted to an Iranian paediatric hospital. Methods: Clinical and microbiological data of patients with positive blood cultures were collected from March 2011 to September 2016. Standard laboratory methods were used for blood culture and bacterial identification. Antimicrobial sensitivity was evaluated by the Kirby–Bauer disk diffusion and broth microdilution methods. Results: Of 2325 bacterial pathogens isolated from blood cultures, 41.1% ( n  = 956) were GNB. Most clinical isolates ( n  = 208; 21.8%) were identified in the cardiac intensive care unit. Predominant bacterial isolates were Klebsiella pneumoniae subsp. pneumoniae ( n  = 263; 27.5%), Escherichia coli ( n  = 192; 20.1%), Serratia marcescens ( n  = 151; 15.8%), Pseudomonas aeruginosa ( n  = 111; 11.6%) and Enterobacter spp. ( n  = 100; 10.5%). Enterobacter isolates showed a high level of ampicillin resistance. Escherichia coli were highly resistant to chloramphenicol (100%), cefixime (100%), ceftriaxone (100%) and ampicillin (96%). Cefixime had the least efficacy against Haemophilus spp. (100% resistant). All K. pneumoniae (100%) were ampicillin-resistant. All S. marcescens were ceftazidime-resistant. No Acinetobacter baumannii were resistant to colistin. All P. aeruginosa were resistant to cefotaxime and trimethoprim/sulfamethoxazole. Conclusions: These results demonstrate the increasing trend in antibiotic resistance among GNB associated with BSI in children, emphasising the importance of continuous screening and surveillance programmes for detection of antibiotic resistance in BSI pathogens for selection of appropriate treatment regimens.